Dynamics in language from a linguistic and neurocognitive perspective - Sakowski, Krzysztof (Acta Universitatis Lodziensis. Folia Germanica, 2025)
Cognitive sciences are grouped together according to their substantial disciplines such as neurobiology, psychology, linguistics and many others. From more than ten years a search has been undertaken for the best fitting cognitive research method, that does not influence the scientific output. More recently attention has been turned to systems which might operate through their dynamic aspect, called the dynamic approach. Their great advantage is to see the old linguistic axioms such as connectivity in a new way.